Calculation of the Resistance of Soils of the Base (Eurasian Scientific Herald, 2022)
This article describes the physical and mechanical properties of soils, deformation of buildings and structures erected on saline and subsidence soils. This article describes the defomation of buildings and structures as a result of brittle and deformed soil and changes in the physical mechanical properties of the around